Unusual variability of isomers in copper() complexes with 1,8-bis(2-hydroxybenzyl)-cyclam - Ma ar, Milan; Faltejsek, Jan; Bušková, Hana; Kolá ná, Lucie; Jaroš, Adam; Kotek, Jan; Straka, Michal; Kubí ek, Vojt ch; Ludvík, Ji í (Dalton transactions : an international journal of inorganic chemistry, 2025)
Copper isotopes and their complexes are intensively studied due to their high potential for applications in radiodiagnosis and radiotherapy. Here, we study the Cu II complex of 1,8-bis(2-hydroxybenzyl)-cyclam (H 2 L), which forms an unexpected variety of isomers differing in the mutual orientation of the substituents on the cyclam nitrogen atoms, the protonation of the phenolate pendant, and the ligand denticity. The interconversion of the isomers is rather slow, which made the isolation, identification and investigation of some of the individual species possible. The most stable and the most common form is the hexacoordinated trans - III isomer. However, several other forms were also observed in solution in the course of HPLC, UV-VIS and electrochemical measurements. The isomers present in solution were identified by comparison with the solid-state structures solved by X-ray diffraction analysis on single crystals and with the help of theoretical calculations. The phenolate pendant is coordinated both in the protonated and deprotonated state; however, the coordination in the axial position of the hexacoordinated trans - III complex is weak, especially in its protonated state. Conversely, the Cu II ion is pentacoordinated in the cis - V isomer with only one phenolate strongly coordinated in the basal plane of the distorted tetragonal pyramid. The computational data showed that the phenolate groups might form strong intraligand hydrogen bonds competitive with the metal-phenolate bonds, stabilizing the structure of the complex. In addition, theoretical calculations revealed that several geometries are energetically close to the optimal one, which indicates possible dynamic behaviour of the complex in solution. The Cu II complex of 1,8-bis(2-hydroxybenzyl)-cyclam forms an unexpected variety of isomers differing in the mutual orientation of the substituents on the cyclam nitrogen atoms, protonation of the phenolate pendant, and the ligand denticity.